2008
DOI: 10.1007/s12010-008-8162-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lignocellulosic Wastes for Production of Edible Mushrooms

Abstract: The degradation of lignocellulosic wastes such as paddy straw, sorghum stalk, and banana pseudostem was investigated during solid-state fermentation by edible mushrooms Pleurotus eous and Lentinus connotus. Biological efficiency of 55-65% was observed in paddy straw followed by sorghum stalk (45%) and banana pseudostem (33%) for both fungal species. The activity of extracellular enzymes, namely cellulase, polyphenol oxidase, and laccase, together with the content of cellulose, lignin, and phenols, was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…For instance, after treatment of various lignocellulosic materials with P. ostreatus, the lignin content decreased by only 23-30% (Rani et al, 2008). Our findings are consistent with the welldocumented ability of mycelia of Pleurotus species to synthesize hydrolytic and oxidative extracellular enzymes including laccase and manganese peroxidase (Olfati and Peyvast, 2008).…”
Section: Delignification and In Vitro Digestibilitysupporting
confidence: 89%
“…For instance, after treatment of various lignocellulosic materials with P. ostreatus, the lignin content decreased by only 23-30% (Rani et al, 2008). Our findings are consistent with the welldocumented ability of mycelia of Pleurotus species to synthesize hydrolytic and oxidative extracellular enzymes including laccase and manganese peroxidase (Olfati and Peyvast, 2008).…”
Section: Delignification and In Vitro Digestibilitysupporting
confidence: 89%
“…genus can be utilised for the delignification of waste materials developed in the course of agricultural production (Cohen et al 2002). The usefulness of various celluloseand lignin-containing materials for mushroom cultivation was confirmed by the research results of a number of researchers (Zervakis et al 2001, Ozcelik and Peksen 2007, Rani et al 2008, Akeviae et al 2009, Dundar et al 2009). The aim of this experiment was to assess mycelium growth and the development of wild strains of P. ostreatus on substrates from flax and hemp shives and compare the obtained results with the mycelium growth of the above-mentioned strains on substrates from deciduous tree sawdust as well as wheat and rye straw commonly employed in the commercial cultivation of the oyster mushroom in our country.…”
Section: Introductionmentioning
confidence: 78%
“…There was a correlation between spawn running and primordial initiation during weeks 3 to 4. Rani et al (2008) showed high cellulase, laccase, and polyphenol oxidase activity during this period and attributed it to the need for carbohydrates by fungal mycelia for sporophore and fruiting body formation. The TP bounce back (but not by more than 25 g GAE/100 g) may have been caused by active mycelial growth, which increases carbon dioxide in the substrate, suppressing other organisms involved in the degradation of phenolic derivatives.…”
Section: Fig 1 Gc-ms Analyses For the Determination Of The Phenolicmentioning
confidence: 87%
“…The TP bounce back (but not by more than 25 g GAE/100 g) may have been caused by active mycelial growth, which increases carbon dioxide in the substrate, suppressing other organisms involved in the degradation of phenolic derivatives. This might cause temporary accumulation of degraded total soluble phenol in the EFBs (Rani et al 2008). Reduction of TP and the absence of phenol in samples at the end of cultivation, after 25 weeks (end of Stage IV in Fig.…”
Section: Fig 1 Gc-ms Analyses For the Determination Of The Phenolicmentioning
confidence: 99%